Programmed Cell Death in Stigmatic Papilla Cells Is Associated With Senescence-Induced Self-Incompatibility Breakdown in Chinese Cabbage and Radish - Huang, Jiabao; Su, Shiqi; Dai, Huamin; Liu, Chen; Wei, Xiaochun; Zhao, Yanyan; Wang, Zhiyong; Zhang, Xiaowei; Yuan, Yuxiang; Yu, Xiaolin; Zhang, Changwei; Li, Ying; et al. (Frontiers in Plant Science, 2020)
Self-incompatibility (SI) is a genetic mechanism flowering plants adopted to reject self-pollen and promote outcrossing. In the Brassicaceae family plants, the stigma tissue plays a key role in self-pollen recognition and rejection. We reported earlier in Chinese cabbage (Brassica rapa) that stigma tissue showed upregulated ethylene responses and programmed cell death (PCD) upon compatible pollination, but not in SI responses. Here we show that senescence causes PCD in stigmatic papilla cells and breaks down SI in Chinese cabbage and in radish. Senescence upregulates senescence-associated genes in Brassica rapa. Suppressing their expression in young stigmas by antisense oligodeoxyribonucleotide abolishes compatible pollination-triggered PCD and inhibits the growth of compatible pollen tubes. Furthermore, ethylene biosynthesis genes and response genes are upregulated in senescent stigmas, and increasing the level of ethylene or inhibiting its response increases or decreases the expression of senescence-associated genes, respectively. Our results suggest that senescence breaks down SI by upregulating ethylene and inducing PCD in stigmatic papilla cells.